CHARACTERISTICS OF WAKALAH CONTRACT IN FINANCING WITH MURABAHAH CONTRACT - A. Junaidi Abdillah; Dyah Ochtorina Susanti; Rahmadi Tektona (Warmadewa Press, 2022)
Act Number 21 of 2008 about Islamic Banking regulates that one of the businesses of Islamic commercial banks is to channel financing under a murabahah contract. Fatwa of the National Sharia Council – MUI No. 04/DSN-MUI/IV/2000 concerning Murabahah regulates the mechanism for granting authorization to customers by banks, to purchase goods from third parties and the murabahah sale and purchase contract must be carried out after the goods, in principle, become the property of the bank. The purpose of this study is to understand, describe, and find the suitability of the characteristic mechanism in financing with murabahah contracts with Fatwa and the provisions of Islamic bank regulators. This research method is normative juridical with a statutory and comparative approach. The research methodology used is doctrinal legal research. Doctrinal legal research is the study of legal rules, principles, concepts or doctrines. In this study, it was found that the characteristics of wakalah contracts in murabahah financing are as a means of granting power of attorney to purchase murabahah objects by customers as proxies from the bank, to then be handed back to the bank and then sold to customers under a murabahah contract.